Diversity Manipulation of Psychrophilic Bacterial Consortia for Improved Biological Treatment of Medium-Strength Wastewater at Low Temperature - Augelletti, Floriana; Jousset, Alexandre; Agathos, Spiros N.; Stenuit, Benoit (Frontiers in Microbiology, 2020)
Psychrophilic bacteria are valuable biocatalysts to develop robust bioaugmentation formulations for enhanced wastewater treatment at low temperatures or fluctuating temperature conditions. Here, using different biodiversity indices (based on species richness (SR), phylogenetic diversity (PD) and functional diversity (FD)), we studied the effects of microbial diversity of artificial bacterial consortia on the biomass gross yields (measured through OD600) and removal efficiency of soluble chemical oxygen demand (mg sCOD removed/mg sCOD introduced) in synthetic, medium-strength wastewater. Combinatorial experiments were used to manipulate biodiversity by assembling artificial consortia (from monocultures to polycultures) using six bacterial strains isolated from cold-room facilities at 4 °C. The increase of species richness resulted in improved sCOD removal efficiency (i.e., 0.266 ± 0.146, 0.542 ± 0.155, 0.742 ± 0.136, 0.822 ± 0.019 for mono-, tri-, penta- and hexacultures, respectively) and higher biomass gross yields (i.e., 0.065 ± 0.052, 0.132 ± 0.046, 0.173 ± 0.049, 0.216 ± 0.019 for mono-, tri-, penta- and hexacultures, respectively). This positive relationship between biodiversity, sCOD removal and biomass gross yield was also observed when considering metabolic profiling (functional diversity) or evolutionary relationships (phylogenetic diversity). A positive effect of biodiversity on sCOD removal efficiency was due to the selection of a particular, best-performing species (i.e., Pedobacter sp.), but also to the presence of complementary use of carbon resources among consortia members (i.e., complementarity effects). Among the biodiversity indices, PD diversity metrics explained higher variation in sCOD removal than SR and FD diversity metrics. For a more effective bioaugmentation, our results stress the importance of using more diverse consortia, with an increased degradation ability, instead of single pure cultures. Moreover, PD could be used as an assembly rule to guide the composition of mixed cultures for wastewater bioaugmentation under psychrophilic conditions.